Systemic cytokine and viral antigen-specific responses in hepatitis D virus RNA positive versus HDV RNA negative patients - Joshi, Shivali S.; Sadler, Matthew; Patel, Nishi H.; Osiowy, Carla; Fonseca, Kevin; Coffin, Carla S. (Frontiers in Medicine, 2023)
Background Hepatitis B virus (HBV)/Hepatitis D Virus (HDV) co-infection increases the risk of severe liver disease compared to HBV mono-infection. Adaptive immune responses to HDV are weakly detectable, and the involvement of innate immunity in the progression of HDV-related liver fibrosis is suggested. We hypothesize that an overall innate immune activation in HBV/HDV co-infection plays a role in liver disease progression and also impacts virus specific T cell response. Methods Sixteen HBV/HDV-co-infected-patients (median age 42y/7F/6 Asian/4 White/6 Black/15 HBeAg-) and 8 HBV monoinfected-patients (median age 39y/4F/4 Asian/3 Black/1 White/HBeAg-) with median follow-up of 5 years were enrolled. Liver fibrosis was assessed by liver stiffness measurement (LSM, FibroScan®). Proliferation of CD3 + CD4+ T cells in response to viral antigens using CFSE assays and cytokine secreting monocytes was analyzed by flow cytometry. Results Of 16 HBV/HDV, 11 were HDV-RNA+ (HBV-DNA 0–1,040 IU/mL), 5/11 Interferon (IFN) + Nucleos/tide Analog (NA), 3/11 NA monotherapy, median ALT 77 U/L at the time of sample collection, median LSM of 9.8. In 5 HDV RNA−, median HBV DNA 65 IU/mL, 4/5 prior IFN and/or NA, ALT 31 U/L, and median LSM 8.5 kPa. In 8 HBV controls, median HBV-DNA, ALT, LSM was 69 IU/mL, 33 U/L,5 kPa, respectively. PBMC stimulation with HBV core antigen (HBcAg) and HDV antigen (HDAg) showed weaker CD3 + CD4 + T-cell proliferation in HDV-RNA+ vs. HDV RNA− and HBV-mono-infected patients (p < 0.05). In HDV-RNA+ patients, a correlation between ALT and TNF-α (r = 0.76, p = 0.008), higher IL-10 levels and increased proportion of CD14 + TNF-α+ cells were found. Conclusion In summary, during HBV/HDV coinfection, HDV RNA+ patients had weaker HBV and HDV specific responses, associated with increased TNF-α + monocytes irrespective of IFN treatment.